A nonlinear elasto-plastic analysis of Reissner-Mindlin plates by finite element method - Meftah Kamel; Sedira Lakhdar (Fracture and Structural Integrity)
In this paper, a finite element simulation of nonlinear elasto-plastic deformations of Reissner-Mindlin bending plates is described. The previously proposed four-node Q4( element with transverse energy of shearing for thick bending plates is extended to account for isotropic material nonlinearities. An incremental finite element procedure has been used for the elasto-plastic analysis of the thick bending plate. Modified Newton-Raphson method has been used to solve the nonlinear equations. Von-Mises yield criteria have been applied for yielding of the materials along with the associated flow rule. To verify the present element, simple tests are demonstrated and various elasto-plastic problems in which the development of the plastic zone are solved